Cost-Effectiveness and Formulary Evaluation: Imaginary Worlds and Entresto Claims in Heart Failure - Paul C Langley (University of Minnesota Libraries Publishing, 2016)
The Program in Social and Administrative Pharmacy at the University of Minnesota recently released its proposed guidelines for formulary evaluation. The guidelines were focused on ensuring that comparative claims made for pharmaceutical products and devices rested on a credible evidence base. The argument was put forward that if value claims for clinical and cost-effectiveness outcomes were to be accepted then they had to be empirically evaluable. The purpose of this commentary is to explore alternative modeled claims for Entresto, an angiotensin receptor neprilysin inhibitor, versus the standard of care with an ACE inhibitor in patients with chronic heart failure. Two models are compared: a lifetime cost-per-QALY model and a 3-year cost and budget impact model. The primary reason for this comparison is the puzzling feature that for a product which is over 120 time as expensive compared to the standard of care (Entresto $380 per month vs. ACE inhibitor $3 per month) the modeled claim can be made that the product is, in willingness to pay terms, cost-effective. The analysis illustrates that, perhaps not surprisingly, different models can generate quite different perspectives on the presumption of 'cost-effectiveness'. In the present case the simple decision model yields a breakeven monthly cost for Entresto of only $23.74. If modeled claims are to be useful for formulary decision making, then we need to eschew 'black box' models with non-evaluable claims in favor of those models that yield credible, evaluable and replicable claims that can support defensible product placement and pricing decisions. Conflict of Interest None   Type: Commentary